Estudio de los factores necesarios para la elaboración de la marca turística para el cantón Gonzanamá, provincia de Loja. - Figueroa Cueva, Andrea Lizzeth (2023)
The canton Gonzanamá is one of the 16 cantons that make up the province of Loja, is known as the agricultural, livestock and craft capital of the province, in turn its people are dedicated to the preparation of dairy products such as cheese, cheese and yogurt, also has a variety of natural and cultural attractions. To comply with the research, the following general objective related to determine the necessary factors for the development of the tourism brand for the canton of Gonzanamá, province of Loja and two specific objectives that are, first determine the tourism potential for the composition of the tourism brand of the canton Gonzanamá, which allowed an assessment of the destination to obtain its main tourism attributes for the development of the tourism brand, also interviews were conducted mainly to local actors related to tourism to determine the tourism potential of the canton; For the second objective related to establishing the factors that will be part of the composition of the tourism brand, a SWOT matrix was made to determine the current situation of the canton and finally with all the information obtained, the brand pyramid was elaborated, derived from the Branding methodology for tourism destinations of the World Tourism Organization, which as a result determined the elements that would make up the design of the brand. In conclusion, it was possible to establish the characteristics that are referents from the five levels of the pyramid of destination branding and that will later serve for the design of the brand giving a great value of cultural identity to the canton and its promotion.